2014
DOI: 10.1155/2014/236361
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island Methylator Phenotype and Prognosis of Colorectal Cancer in Northeast China

Abstract: Purpose. To investigate the association between CpG island methylator phenotype (CIMP) and the overall survival of sporadic colorectal cancer (CRC) in Northeast China. Methods. 282 sporadic CRC patients were recruited in this study. We selected MLH1, MGMT, p16, APC, MINT1, MINT31, and RUNX3 as the CIMP panel markers. The promoter methylation was assessed by methylation sensitive high resolution melting (MS-HRM). Proportional hazards-regression models were fitted with computing hazard ratios (HR) and the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
(111 reference statements)
1
25
2
Order By: Relevance
“…Results of previous studies on the role of chemotherapy in CIMP status subgroups were inconsistent. Li et al (2014) did not find an association between chemotherapy and OS for both CIMP-H and CIMP-L/N patients. Jover et al (2011) found that among stage II and III CRC patients chemotherapy was associated with significantly better DSS among CIMP-L/N patients (HR=0.4; 95% CI=0.2–0.6) but not among CIMP-H CRC patients (HR=0.8; 95% CI=0.3–2.0).…”
Section: Discussionmentioning
confidence: 90%
“…Results of previous studies on the role of chemotherapy in CIMP status subgroups were inconsistent. Li et al (2014) did not find an association between chemotherapy and OS for both CIMP-H and CIMP-L/N patients. Jover et al (2011) found that among stage II and III CRC patients chemotherapy was associated with significantly better DSS among CIMP-L/N patients (HR=0.4; 95% CI=0.2–0.6) but not among CIMP-H CRC patients (HR=0.8; 95% CI=0.3–2.0).…”
Section: Discussionmentioning
confidence: 90%
“…The incidence and mortality rate of CRC in China have increased rapidly over the past several decades [21]. In order to improve clinical prognosis of CRC patients, it is necessary to screen useful diagnostic and prognostic biomarkers of CRC, which can contribute to early diagnosis and improve the management of individualized treatment [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies (Lee et al, 2008;Barault et al, 2008;Kim et al, 2009;Rhee et al, 2012;Li et al, 2014;Kang et al, 2015) showed a significant decrease in the OS of CIMP+ patients. The study of Barault et al (2008) showed no increase in the OS in the CIMP+ MSS and KRAS wild-type subgroup.…”
Section: Colorectal Cancer Cimp± All Stagesmentioning
confidence: 99%